(untitled) (Konferensiyalar | Conferences, 2024)
Learning a new language is challenging and requires careful planning to achieve success. This thesis aims to explore the various factors that contribute to effective language learning, with a focus on motivation and monitoring. By understanding these key elements, language learners can develop effective strategies to enhance their language acquisition skills. Firstly, students know their motivation and goals. The next important thing is their language levels.